LINGUOCULTURAL CODE OF THE MAIN DIRECTIONS OF THE DOCTRINE «NATIONAL SPIRIT - WORLD HEIGHTS» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article presents a linguistic analysis of the main directions of the doctrine “National Inspiration - World Excellence”, adopted on December 18, 2024, and its interpretation as a linguistic and cultural code. The Kyrgyz people are a people with a rich history. Therefore, for centuries they have passed on their philosophical thoughts from generation to generation through their traditions and rituals. These ideas are currently studied in science as “codes”. The role of the linguistic code in intercultural communication will be discussed.
Keywords: language, nation, culture, code, sign, tradition, idea, development.